Wide-angle X-ray scattering and molecular dynamics simulations of supercooled protein hydration water. Issue 34 (16th July 2021) - Bin, Maddalena; Yousif, Rafat; Berkowicz, Sharon; Das, Sudipta; Schlesinger, Daniel; Perakis, Fivos
Abstract : We investigate hydrated proteins by decomposing the water and protein components and we observe that the protein signal is nearly temperature independent, whereas that of hydration water exhibits a trend similar to bulk water. Abstract : Understanding the mechanism responsible for the protein low-temperature crossover observed at T ≈ 220 K can help us improve current cryopreservation technologies. This crossover is associated with changes in the dynamics of the system, such as in the mean-squared displacement, whereas experimental evidence of structural changes is sparse. Here we investigate hydrated lysozyme proteins by using a combination of wide-angle X-ray scattering and molecular dynamics (MD) simulations. Experimentally we suppress crystallization by accurate control of the protein hydration level, which allows access to temperatures down to T = 175 K. The experimental data indicate that the scattering intensity peak at Q = 1.54 Å −1, attributed to interatomic distances, exhibits temperature-dependent changes upon cooling. In the MD simulations it is possible to decompose the water and protein contributions and we observe that, while the protein component is nearly temperature independent, the hydration water peak shifts in a fashion similar to that of bulk water. The observed trends are analysed by using the water–water and water-protein radial distribution functions, which indicate changes in the local probability density of hydration water.